Analysis of the Teaching Professional Code of Ethics and its Implications in Teaching Practice - Ningrum, Adiya Putri Satya; Yulianti, Anggelika Devi; Dewi, Dieva Tri Eugieta; Mahardika, I Ketut; Setiyowati, Rendike Aulia (International Journal of Education, Information Technology, and Others, 2024)
The Code of Professional Ethics for Teachers is a guideline and moral foundation for the professional behavior of teachers, including supervising teachers and consultants. The importance of a professional code of ethics is to improve organizational ethics so that individuals behave ethically. In teaching practice, the teacher's professional code of ethics has a very significant meaning, because it can influence the quality of education that students receive. The teacher's code of ethics is designed to provide behavioral guidelines for teachers wherever and under any conditions. Teachers play a very important role in implementing and achieving national education goals. The role of a teacher is very clear and cannot be replaced by anyone, especially in a multicultural and multidimensional society. The successful implementation of professional teacher education also depends greatly on the quality of teaching involved in providing learning to prospective students. Professional ethics are very important to improve the quality of national education. A teacher is considered professional if they comply with the established Teacher Code of Ethics. This research method is qualitative research which focuses on literature research and includes several journals. The results of this research indicate the existence of a code of ethics and its application in the teaching practice of the teaching profession